GRAPPA 2024 Meeting: Advances in Psoriatic Disease Research From Pilot Grant Awardees - Colaco, Keith; Alzayat, Omar; Dang, Steven; Gross, Caroline; Helliwell, Philip S.; Karmacharya, Paras; Simon, David; Svedbom, Axel; Chandran, Vinod; Liao, Wilson; de Vlam, Kurt (Journal of Rheumatology, 2025)
Prioritizing and supporting trainee research in psoriatic disease (PsD) is a cornerstone of the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA). Each year, trainees and junior faculty are invited to submit proposals to GRAPPA to fund pilot research projects related to psoriasis or psoriatic arthritis. Projects can be in any of the following 4 categories: clinical science, translational science, basic science research, or combined PsD. GRAPPA remains committed to showcasing the trainee research supported by these grants at the annual meeting. The GRAPPA 2024 annual meeting and trainee symposium was held in Seattle, Washington, USA; a meeting highlight was the session dedicated to the pilot research grant projects led by trainees and faculty. This year, 27 submissions were received from 14 countries across North America, Europe, and Asia. Compared to prior years, an updated grant review process enhanced efficiency and created more opportunities for conversation among evaluators. A panel of 14 GRAPPA reviewers assessed the submissions, ultimately selecting 4 projects for funding. This meeting report aims to summarize the 2024 pilot research grant recipients and the project results from past grant recipients.
CRIS-Team Scopus Importer:2025-12-12
Keywords: biomarker; GRAPPA; psoriasis; psoriatic arthritis